Use of ratings of perceived exertion in sports - Eston, R. (International Journal of Sports Physiology and Performance, 2012)
The rating of perceived exertion (RPE) is a recognized marker of intensity and of homeostatic disturbance during exercise. It is typically monitored during exercise tests to complement other measures of intensity. The purpose of this commentary is to highlight the remarkable value of RPE as a psychophysiological integrator in adults. It can be used in such diverse fashions as to predict exercise capacity, assess changes in training status, and explain changes in pace and pacing strategy. In addition to using RPE to self-regulate exercise, a novel application of the intensity:RPE relationship is to clamp RPE at various levels to produce self-paced bouts of exercise, which can be used to assess maximal functional capacity. Research also shows that the rate of increase in RPE during self-paced competitive events of varying distance, or constant-load tasks where the participant exercises until volitional exhaustion, is proportional to the duration that remains. These findings suggest that the brain regulates RPE and performance in an anticipatory manner based on awareness of metabolic reserves at the start of an event and certainty of the anticipated end point. Changes in pace may be explained by a continuous internal negotiation of momentary RPE compared with a preplanned "ideal rate of RPE progres- sion" template, which takes into account the portion of distance covered and the anticipated end point. These observations have led to the development of new techniques to analyze the complex relationship of RPE and pacing. The use of techniques to assess frontal-cortex activity will lead to further advances in understanding.